Forces impulse of body parts as function for prediction of total impulse and performance point of ippon Seoi Nage skill in judo - Fawzi Mustafa, I. (World Journal of Sport Sciences, 2010)
The research aims to recognize contribution percentage of forces impulse of body parts in total impulse for center of gravity (CG.) and performance point to Ippon Seoi Nage (I.S.G.) skill, research sample was selected purposely, it included 7 players of 17- 20 years, the researcher used (3D) video recording system using two Panasonic video cameras of light resource with frequency of 25 field/sec. dynamic analysis using Win analyze system and Jury arbitration, of the most important results gained by the researcher was contribution percentage of selected variables in total impulse for of (CG.) and performance point of the skill under discussion, the most important conclusions was that contribution rate at Kuzushi phase is the resultant of trunk impulse and the resultant of right thigh impulse and at Tsukuri phase, the resultant of trunk and thighs impulse was the highest contribution rate in the resultant of total impulse for (CG.), while performance time and the resultant of left thigh impulse were the highest contribution percentage at Kake phase, the resultant of right and left thighs impulse at Tsukuri phase and both the resultant of trunk and right thigh impulse during the Kuzushi phase had the highest contribution percentage in performance point of (I.S.G.) skill, performance point could be predicted by the following equation: Performance point of (I.S.G.) skill = (7.32) - 2.38 (skill performance time) - 0.06 (the resultant of right thigh impulse during the Kuzushi phase) + 0.056 (the resultant of trunk impulse during the Kuzushi phase) + 0.08 (the resultant of left thigh impulse during the Tsukuri phase) - 0.43 (the resultant of right thigh impulse during the Tsukuri phase) + 0.138 (the resultant of trunk impulse during the Tsukuri phase).